2010
DOI: 10.1007/s10658-010-9710-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a model for management of brown rot in organic apple orchards

Abstract: Temporal development of brown rot (Monilinia fructigena) on fruits was analysed in two organic apple orchards on three apple cultivars in Eastern Hungary from 2002 to 2006. The threeparameter logistic function gave the best fit to brown rot over four non-linear growth functions in all cultivars, years and orchards. Depending on location, year and cultivar, disease increased continuously from 6 to 8 weeks before harvest up to harvest, reaching 19-37% of disease incidence. Disease variables of Y f , the final di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Seeing high brown rot incidence level at harvest, an improtant task is to further improve both insect and frungal disease managements in organic fruit production. A succesful example of this was a development of brown rot management strategy in organic apple production by Holb et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Seeing high brown rot incidence level at harvest, an improtant task is to further improve both insect and frungal disease managements in organic fruit production. A succesful example of this was a development of brown rot management strategy in organic apple production by Holb et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…• check reference of historical weather to decide if fungicide application is needed; • and spray fungicide immediately. In a more recent study Holb et al (2011) prepared a brown rot forecasting disease management strategy for M. fructigena for organic apple orchard. In this five-year-study, temporal development of brown rot on fruits was analysed in two organic apple orchards.…”
Section: Disease Warning Modelsmentioning
confidence: 99%
“…Insect dispersal of conidia has also been an importamt factor from one fruit to another (Croxall et al, 1951;Lack, 1989). Studies demonstrated a low aerial concentration of M. fructigena in integrated apple orchards (Van Leeuwen et al, 2000;Xu et al, 2001;Holb, 2008b) while in organic apple orchards high conidial concentration were recorded (Holb, 2008b;Holb et al, 2011). Previous studies showed that viability of trapped conidia was 60 % (Holb, 2008b).…”
Section: Introductionmentioning
confidence: 98%